KARAKTERISTIK STOMATA NYAWAI (Ficus variegata Blume) DARI 3 SUMBER BENIH ASAL KALIMANTAN DI KHDTK RIAM KIWA DESA LOBANG BARU - Rahmah Rahmah; Normela Rachmawati; Eny Dwi Pujawati (Jurnal Sylva Scienteae, 2022)
This study aims to calculate the density of stomata, identify the state of stomata and measure the length and width of the stomata of the leaves of the leaves (Ficus variegata Blume) of 3 different seed sources. The research was conducted at the Biology Laboratory of FMIPA ULM Banjarbaru and leaf sampling at Riam Kiwa KHDTK Lobang Baru Village, District. Mataraman, Banjar Regency, South Kalimantan, for 6 months. Data were analyzed using. Data were analyzed using RAL (Completely Randomized Design). The resulting density of stomata is known from South Kalimantan, East Kalimantan and Central Kalimantan seed sources on the underside surface with aninositic type, with a large average density of Central Kalimantan seed sources because of genetic influences. Stomata of life leaves are stomata that have open stomata and closed stomata. Most plants with low CO2 concentrations in the leaves, will make the stomata open. Conversely, high CO2 concentrations in leaves cause the stomata to partially close, with a percentage of seed sources from South Kalimantan at 12% open stomata, East Kalimantan 7.19% open stomata, and Central Kalimantan 13.8% open stomata and there are also closed stomata conditions . The length and width of the stomata with the average leaf source from South Kalimantan with a length of 11.68 µm and a width of 2.78 µm, the source of seeds from East Kalimantan is 11.87 µm long and 2.75 µm wide. And for the length and width of seed sources from Central Kalimantan, which are 12.3 µm and 3.61 µmPenelitian ini bertujuan untuk menghitung kepadatan stomata, identifikasi keadaan stomata dan Ukur panjang dan lebar stomata daun nyawai (Ficus variegata Blume) 3 sumber benih berbeda. Penelitian ini dilakukan di Laboratorium Biologi FMIPA ULM Banjarbaru dan pengambilan sampel daun di Riam Kiwa KHDTK Desa Lobang Baru, Kecamatan. Mataraman, Kabupaten Banjar, Kalimantan Selatan, selama 6 bulan. Data dianalisis menggunakan. Data dianalisis menggunakan RAL (Rancangan Acak Lengkap). Hasil kerapatan diketahui stomata nyawai dari sumber benih Kalimantan Selatan, Kalimantan Timur dan Kalimantan Tengah terdapat dipermukaan bawah daun dengan tipe aninositik, dengan rata-rata kerapatan yang besar yaitu pada sumber benih Kalimantan Tengah karena dipengaruhi genetik. Keadaan stomata daun nyawai yaitu terdapat stomata yang terbuka dan stomata tertutup. Sebagian besar tumbuhan konsentrasi CO2 yang rendah di daun, akan membuat stomata membuka. Sebaliknya konsentrasi CO2 yang tinggi di daun menyebabkan stomata menutup sebagian, dengan presentase sumber benih asal Kalimantan Selatan sebesar 12% stomata terbuka, Kalimantan Timur 7,19% stomata terbuka, dan Kalimantan Tengah 13,8% stomata terbuka dan ada juga keadaan stomata yang tertutup. Ukuran panjang dan lebar stomata dengan rata-rata daun sumber asal Kalimantan Selatan dengan panjang 11,68 µm dan lebar 2,78 µm, sumber benih asal Kalimantan Timur yaitu panjang 11,87 µm dan lebar 2,75 µm. Dan untuk ukuran panjang dan lebar sumber benih asal Kalimantan Tengah yaitu 12,3 µm dan 3,61µm